Regulação técnica para se obter melhor eficiência na motorização de pequenas centrais hidrelétricas no Brasil - Miranda, Roberto Lobo (2009)
This study s purpose is to discuss an eventual increase in the electrical energy production that is defined for small-scale hydroelectric power plants (SPP), so that the choosing of the type of turbine becomes a tool in terms of expanding the offer of energy from the same hydroelectric power source used. The present work is concerned with the so called low head waterfalls hydroelectric power plant type and highlights the role played by those plants in a scenario that prevails the exploration of the falling water hydroelectric power plant type in substitution of those that makes use of big reservoirs. It suggests that the variety of turbine types constructed according to the Kaplan family conception should receive priority during the plants project analysis and during the solution application s process. For this reason, it is presented its efficiency and operational flexibility in relation to other existing arguments. As for the methodology, this research consisted of a selection and evaluation of 17 hydroelectric projects, being all of them fit in the SPP category. Based on the information found on technical records, on the respective hydroelectric projects summaries and on the accepted criteria that deals with the amount of energy that can be commercialized by the SHP, besides the monthly average flow, it was tried to identify in to what extent it would be possible to have a greater electrical energy exploration from the hydroelectric power plant that has a daring technical arrangement, sustained by the Kaplan family turbines technical evolution. The obtained results indicated that a change in the projects evaluation. A hydroelectric power plant, considered as a public good, must maximize as much as possible the hydroelectric power source in use, being it at the moment of the construction or in the future. Energy losses can not occur given to long term justified economic or financial contexts permitting losses along the hydroelectric power plant economic exploration. This work also presents complementary studies related to hydroelectric power plant implantation costs as well as contract forms, as a way of subsidizing supplementary energy gains, but those are also contextualized values. In terms of giving more sensibility to this work, its was presented an analysis of the quantity of residences that could be beneficiated by the obtained energy gains, such as: the summer time implantation. As for the results, it were presented parameters that provoke questions that are susceptible for project s definitions concerning the energy industry agents, making it possible the project s performance improvement and the stimulation of technological advances to hydraulic generation machineries.